The Law of Returning Dowry in The Banggai Tradition - Mahmud Sakka, St. Samsuduha; Sakirah, Sakirah; Rasdiana, Rasdiana (Journal of Law, Politic and Humanities, 2024)
Research Objective: This research aims to examine the Law of Dowry Return in Banggai Tradition. Theory: This research used Gustav Radbruch's Legal Objective Theory, which has three basic assumptions of legal objectives, namely: justice, expediency, and legal certainty, and all three are legal objectives mutually. Method: This research is a qualitative research using the Legal Pluralism Paradigm. Results of the Research: Banggai, as a former Islamic Sultanate that had existed since the end of the 16th century, inherited many tangible and intangible legacies that can still be found in the community today. One of them is the Law of Dowry Return in Banggai Tradition, a tradition that is still alive in the midst of the community, and becomes an unwritten legal norm, which applies in a particular community environment (hybrid law or unnamed law). The research is objectively analytical, which means that customary law is studied positively and negatively. This research found that the law of returning dowry still remains valid in the Banggai community, both Muslims and Christians.